Impact of Recreational Activities on Employee Productivity of Nepalese Commercial Banks - Suwal, Rohish; Uprety, Pravat (Journal of Business and Social Sciences Research, 2023)
This study aims to analyse the impact of recreational activities on employees’ productivity of Nepalese commercial banks as well as to examine the relationship between “physical fitness activities and employees’ productivity”, “mental health activities and employees’ productivity”, and “Entertainment activities and employees’ productivity.” To carry out this research, 201 samples were gathered who were the employees working in Nepalese commercial banks inside the Kathmandu valley. Quota sampling technique was applied to acquire the data from different categories of commercial banks. Primary sources of data have been used for the study along with cross sectional research design. Structured questionnaire was also designed and used for the study. It concluded that there is a moderate positive relationship between each independent variable, i.e., physical fitness activities, mental health activities and entertainment activities and dependent variable, i.e., employees’ productivity. However, in terms of analysing the impact of independent variables on the dependent variable, it showed that two independent variables, i.e., physical fitness activities and entertainment activities have a significant positive impact on employee productivity. When employees are productive, the organisation is also productive. As there is a positive impact of recreational activities on employees’ productivity, all the commercial banks need to focus on recreational activities. Commercial banks who are adopting recreational activities, their future is bright.